Zeami's Buddhism and Noh in Kurosawa's Ikiru - Green, Ronald S. (The journal of religion and film, 2024)
This paper explores the influences of Noh drama theorist Zeami Motokiyo on Akira Kurosawa's 1952 film Ikiru. While Kurosawa's adaptations of traditional Japanese arts are well documented, this study uniquely demonstrates how specific Noh aesthetics shaped this film. It analyzes how Kurosawa's direction of actor Takashi Shimura embodies Zeami's aesthetic principles of awareness of impermanence (mujō), profound mystery (yūgen), and no-mind (mushin), which are performative expressions of Buddhist philosophies. Kurosawa employs four methods developed by Zeami: the use of masks, sparseness in settings and costumes, singing, and the application of an actor's inner flower. This paper uniquely offers side-by-side visual comparisons of facial expressions in Ikiru with Noh masks, connects passages from Zeami's writings to scenes in the film, and provides in-depth analyses of iconic scenes such as the rabbit, the swing, and the bridge. Additionally, it expands the understanding of Zeami's Buddhist thinking by investigating his Jishū tradition of Buddhism, previously unacknowledged in other research. This study is the first to analyze any of Kurosawa's works in specific terms of Buddhist saṃvega and pasāda, using relevant Buddhist texts.